TI_GERICHTE 52.2021.482 vom 12. November 2021 , Commessa pubblica. Aggiudicazione. Valutazione delle offerte - TI Tribunale d'appello (2021)
Commessa pubblica. Aggiudicazione. Valutazione delle offerte